Around the U of M: Real College Podcast - Radio K (KUOM). University of Minnesota (My University, 2019)
On this episode of the podcast, we look at the goings on around our very own University of Minnesota- Twin Cities campus. Shoe Tree QoTW by Casey McCabe 1:11 Shoveling Snow by Nathan Fervoy 3:56 Rural Design by Rose O'Neil 12:06
Runtime (26:57).